2000
DOI: 10.1016/s0304-3959(99)00205-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of nociceptive transmission by NMDA/glycine site receptor in the ventroposterolateral nucleus of the thalamus

Abstract: NMDA-type glutamate receptors are involved in the generation and maintenance of altered pain states. In the present study, we examined the effect of an NMDA-glycine site antagonist, GV196771A [E-4, 6-dichloro-3-(2-oxo-1-phenyl-pyrrolidin-3-ylidenemethyl)-1H- indole-2- carboxylic acid sodium salt], on responses to noxious stimuli both in normal rats and during peripheral mononeuropathy induced by chronic constriction injury (CCI) of the sciatic nerve. In one series of experiments, activity of nociceptive neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 66 publications
0
24
0
Order By: Relevance
“…Several authors have demonstrated evidence of the efficacy of NMDA receptor antagonists in chronic pain, e.g. neuropathy [11,12,13,14,15,16]. Moreover, NMDA receptor antagonists in combination with opioids have been shown to be more effective than opioids administered alone in different kinds of this pain [17,18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have demonstrated evidence of the efficacy of NMDA receptor antagonists in chronic pain, e.g. neuropathy [11,12,13,14,15,16]. Moreover, NMDA receptor antagonists in combination with opioids have been shown to be more effective than opioids administered alone in different kinds of this pain [17,18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rat neuropathic pain models, as well as physiological studies in humans with chronic pain, have demonstrated abnormal discharge patterns in the thalamus (Guilbaud et al, 1990;Lenz et al, 1994Lenz et al, , 1995. In addition, NMDA receptor antagonists have been shown to reduce nociceptive-induced activity in the thalamus, whereas NMDA antagonism and modulation of metabotropic glutamate receptor signaling at the level of the thalamus block the development of hyperalgesia in both rat and primate neuropathic pain models (Dougherty et al, 1996;Kolhekar et al, 1997;Bordi and Quartaroli, 2000;Neugebauer, 2002;Chiechio et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, NMDA receptor antagonists in combination with opioids have been indicated to be more effective than the former administered alone [16,[18][19][20][21][22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%